A Systematic Review on the Impact of Genetic Testing for Familial Melanoma I: Primary and Secondary Preventative Behaviours - Primiero, Clare A; Yanes, Tatiane; Finnane, Anna; Soyer, H Peter; McInerney-Leo, Aideen M (Dermatology (Basel), 2021)
Increasing availability of panel testing for known high-penetrance familial melanoma genes has made it possible to improve risk awareness in those at greatest risk. Prior to wider implementation, the role of genetic testing in preventing melanoma, through influencing primary and secondary preventative behaviours, requires clarification. Database searches of PubMed, Embase, CINAHL, PsycINFO and the Cochrane Library were conducted for studies describing preventative behaviour outcomes in response to genetic testing for melanoma risk. Publications describing original research of any study type were screened for eligibility. Eighteen publications describing 11 unique studies were reviewed. Outcomes assessed are based on health behaviour recommendations for those at increased risk: adherence to sun-protective behaviour (SPB); clinical skin examinations (CSE); skin self-examinations (SSE); and family discussion of risk. Overall, modest increases in adherence to primary prevention strategies of SPB were observed following genetic testing. Importantly, there were no net decreases in SPB found amongst non-carriers. For secondary preventative behaviour outcomes, including CSE and SSE, increases in post-test intentions and long-term adherence were reported across several subgroups in approximately half of the studies. While this increase reached significance in mutation carriers in some studies, one study reported a significant decline in annual CSE adherence of non-mutation carriers. Evidence reviewed suggests that genetic testing has a modestly positive impact on preventative behaviour in high-risk individuals. Furthermore, improvements are observed regardless of mutation carrier status, although greater adherence is found in carriers. While additional studies of more diverse cohorts would be needed to inform clinical recommendations, the findings are encouraging and suggest that genetic testing for melanoma has a positive impact on preventative behaviours.